A System Innovation Approach for Science-Stakeholder Interface: Theory and Application to Water-Land-Food-Energy Nexus - Alamanos, Angelos; Koundouri, Phoebe; Papadaki, Lydia; Pliakou, Tatiana (Frontiers in Water, 2022)
The Water-Food-Energy Nexus can support a general model of sustainable development, balancing resources with increasing economic/productive expectations, as e.g. in agriculture. We synthesize lessons from Greece’s practical and research experience, identify knowledge and application gaps, and propose a novel conceptual framework to tackle these challenges. Thessaly (Central Greece), the country’s driest region and largest agricultural supplier is used as an example. The area faces a number of water quantity and quality issues, ambitious production-economic objectives, continuous (historically) drought and flood events, conflicts, administrative and economic issues, under serious climate change impacts. A detailed assessment of the current situation is carried out, covering all these aspects, for the first time in an integrated way. Collaboration gaps among different stakeholders are identified as the biggest impediment to socially acceptable actions. For the first time, to our knowledge, the Nexus is set as a keystone to develop a novel framework to reverse the situation and achieve sustainable management under socially acceptable long-term visions. The proposed framework is based on Systems’ Theory, innovation, uses a multi-disciplinary platform to bring together all relevant stakeholders, provides scientific support and commitment, and makes use of technological advances for the system’s improvement.